Commodity fundamentals : how to trade the precious metals, energy, grain, and tropical commodity markets - Spurga, Ronald C. (Wiley trading series., 2006)
Ronald Spurga has written a straightforward guide for investors working within the highly profitable but complex commodity marketplace.